Characterization of Parylene-C degradation mechanisms: In vitro reactive accelerated aging model compared to multiyear in vivo implantation. (February 2020) - Caldwell, Ryan; Street, Matthew G.; Sharma, Rohit; Takmakov, Pavel; Baker, Brian; Rieth, Loren
Abstract: Implantable neural microelectrodes are integral components of neuroprosthetic technologies and can transform treatments for many neural-mediated disorders. However, dielectric material degradation during long-term (>1 year) indwelling periods restricts device functional lifetimes to a few years. This comprehensive work carefully investigates in vivo material degradation and also explores the ability of in vitro Reactive Accelerated Aging (RAA) to evaluate implant stability. Parylene C-coated Utah electrode arrays (UEAs) implanted in feline peripheral nerve for 3.25 years were explanted and compared to RAA-processed devices, aged in phosphate buffered saline (PBS) + 20 mM H2 O2 at either 67 or 87 °C (28 or 7 days, respectively). Electron microscopy revealed similar physical damage characteristics between explants and RAA (87 °C) devices. Parylene C degradation was overwhelmingly apparent for UEAs from both RAA cohorts. Controls aged in PBS alone displayed almost no damage. Spectroscopic characterization (EDX, XPS, FTIR) found clear indications of oxidation and chlorine abstraction for Parylene C aged in vivo . While in vitro aging was also accompanied by signs of oxidation, changes in the chemistry in vivo and in vitro were statistically different. Analysis of RAA-aged devices identified UEA fabrication approaches that may greatly improve device resistance to degradation. This work underscores the need for an improved understanding of in vivo damage mechanisms, to facilitate the critical need for representative in vitro accelerated testing paradigms for long-term implants.